The equity-financing channel, the catering channel, and corporate investment: International evidence - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 2017)
We examine how stock market mispricing affects corporate investment in an internationalsetting. We find that investment is more sensitive to stock prices for equity-dependent firms thanfor non-equity-dependent firms in our international sample. Investment is also more sensitive tostock prices for firms located in countries with more developed capital markets (i.e., lower costsof raising capital), higher share turnover (i.e., shorter shareholder horizons), and higher R&Dintensity (i.e., more opaque assets). More importantly, the positive relation between equitydependence and the sensitivity of investment to stock prices is more pronounced for firmslocated in these same countries. These findings are consistent with the equity-financinghypothesis and the catering hypothesis on corporate investment proposed by Baker, Stein, andWurgler (2003) and Polk and Sapienza (2009), respectively.